Pembentukan Kepribadian Murid melalui Hubungan Emosional dalam Pendidikan - Achmad Maulidi; Nabilatun Nada; Ali Tohir; Muru'atul Afifah (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2020)
The emotional intelligence of the teacher has an important role in shaping the personality of the student. In this case the emotional intelligence of the teacher becomes the focus in shaping the personality of the student. Therefore researchers conducted research on the role of teacher emotional intelligence in shaping the personality of female students. The focus of this research is to find out how the character formation of female students through the teacher's emotional intelligence and to find out the inhibiting factors. The research findings show that the teacher's emotional intelligence has been able to shape the personality of students at MA Al-Amien I Prenduan, this is because teachers often become figures/examples for their students, but in forming the personality of students, they still experience several obstacles, including from students, discipline and educators.